‘Travelers of unknown path’: on the aim of Islamic Education - Ahmad H.Osman, Rahmah; siddiqui, naseeb (IIUM Press, 2021)
The battle over how to defend the Muslim Ummah and especially youth from modern science and its philosophy has ended up in a dilemma of unsolved misery. On the one hand the rational spirit of the west was blamed as having adulterated Muslim society. However, on the other hand, the long-established way of Muslim education was called in the court of ‘reason’. The allegations of the west became the vehicle for Muslims to criticize their own educational philosophy and re-evaluate it in order to defend it against these onslaughts. It would be biased to call the same reasoning as good for one philosophy but bad for another, the secret paradox. As a result of the above, there was a flood of literature to define what should be the Islamic concept of education which was more as defensive stance than an exercise of pure reason. It is claimed that till now, there is no final answer to the `product’ of Islamic education which can be presented as an alternative to the secular product of `good citizen’. Neither in the name of philosophy nor in terms of a practical framework, have Islamic scholars envisioned a clear product. Thus, until present, the reasoning to define the `aim’ of Islamic education is incoherent and varies in degrees. This article therefore will address these incoherencies in three stages. Firstly, it sketches a cursory view of the initial centuries of Islam where a strange combination of reason and revelation lead to a variant product of Islamic education which was used to establish a premise. Secondly, based on the previous premise, the 19-20th century was analysed by considering three well-known philosophers in order to see the degree of achievements both philosophically and practically. The results from this stage produced once again broad variations in the concept of education. Thirdly, based on the outcomes of the first two stages contrast analysis was done in order to discuss the reasons for lack of and future work to consequently define a true product of Islamic education.